PENGARUH DANA PIHAK KETIGA, BIAYA OPERASIONAL, DAN NON PERFORMING LOAN TERHADAP LABA BERSIH BANK UMUM SWASTA NASIONAL DEVISA PADA BANK INDONESIA - Chairul Ihsan Burhanuddin; Nur Fatwa (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2015)
This study aims to identify and analyze Effect of Third Party Fund, Operating Costs, and Non Performing Loans to Net Income Foreign Exchange Bank BUSN at Bank Indonesia either simultaneously or partially. This study uses secondary data from the Indonesian banking statistics published in the website of Bank Indonesia (BI). This research was conducted using a sample firms that fall into the category of the National Private Commercial Bank Foreign Exchange with the observation period of 2011 - 2013 There were 43 companies listed in the category of Private Banks National Foreign Exchange but only 36 companies that meet the criteria of this study sample. Multiple linear regression analysis method is used to test the hypothesis. The results of this study are the Third Party Fund has a negative and significant effect on Net Income. Operational costs have a positive and significant impact on Net Income. And non performing loans has a negative but insignificant effect on Net Income. These results indicate that the management of third party funds, operating expenses, and non-performing loans must be done optimally by considering the risks as well as the portion of the distribution and acceptance in order to achieve the desired net income.